Intercultural competence development through a tele‐collaborative project supported by speech‐enabled corrective feedback technology - Shadiev, Rustam; Feng, Yingying; Zhussupova, Roza; Huang, Yueh‐Min (Journal of computer assisted learning, 2024)
Background Tele‐collaborative projects serve as invaluable platforms for students from diverse countries to engage in cross‐cultural communication and exchange cultural knowledge. These projects offer immense benefits in terms of fostering intercultural competence among participants. However, one challenge arises when participants engage in spoken communication rather than written. Those who may not share a common first language often rely on a lingua franca such as English for intercultural communication. In such spoken exchanges, varying levels of language proficiency can lead to communication errors that hinder the intercultural learning process and impede the development of intercultural competence in their fellow participants. Objectives In the present trial study, our primary objective was to tackle the language‐related challenge associated with spoken communication head‐on. Our focus centred on addressing the discrepancies arising in spoken communication, and we aimed to mitigate these discrepancies by utilizing speech‐enabled corrective feedback technology. Methods In a tele‐collaborative project involving 28 graduate students from the People's Republic of China and Republic of Kazakhstan, the participants engaged in spoken communication and cultural exchange in English via the internet. Given the emphasis on spoken communication and the recognition that English was not their first language, we implemented a speech‐enabled corrective feedback (SECF) technology to ensure effective communication in terms of pronunciation, grammar, and word choice. The SECF technology detected and provided instant feedback on any speech mistakes, enabling participants to make corrections accordingly. The main aim of our study was to explore the potential benefits of integrating SECF technology into a tele‐collaborative project for the development of participants' intercultural competence. Additionally, we sought to gather insights into the students' perceptions of the SECF support. Results and Conclusions The results of our study revealed significant improvements in the participants' intercultural competence across dimensions such as knowledge, skills, attitude, and awareness. Furthermore, the participants expressed positive perceptions of the SECF technology. Drawing from our findings, we offer valuable implications and recommendations for educators and researchers in the field, enhancing their understanding of the role of SECF technology in supporting intercultural competence development in tele‐collaborative settings. Lay Description What is currently known about the subject matter Tele‐collaborative projects are widely utilized to enhance intercultural competence. Low language proficiency of participants often poses a significant challenge in tele‐collaborative projects. What this paper adds The present study addressed the language barrier by incorporating speech‐enabled corrective feedback (SECF) technology to support our tele‐collaborative project. The study explored how our tele‐collaborative project, supported by SECF, facilitated the development of intercultural competence. The implications of study findings for practitioners Scholars and practitioners should consider implementing SECF technology to address language‐related barriers in tele‐collaborative projects. Guidelines based on our study can be utilized to design tele‐collaborative projects with SECF support. Training on technology and constant support needs to be provided to participants.